Corporate Governance and Environmental Social Governance on Audit Quality - Bangsawan, Hariz Salim (Journal of Creative Student Research, 2026)
This study aims to examine and synthesize the literature on the relationship among corporate governance, Environmental, Social, and Governance, and audit quality, with particular attention to how these variables interact within corporate accountability systems. The study employed a Systematic Literature Review approach guided by PRISMA to ensure a structured, transparent, and traceable review process. The literature search focused on journal publications from 2022 to 2026, and the review process proceeded through identification, screening, eligibility, and inclusion stages. From 249 records identified in the source, 16 studies were retained for final synthesis after applying predefined relevance and eligibility criteria. The results show that the literature converges on a central pattern in which substantive governance mechanisms are more effective than formal governance structures alone in strengthening oversight quality and reducing opportunistic behavior. Audit quality generally plays a constraining role in tax avoidance and strengthens governance effectiveness, although its influence is often conditional on institutional setting, audit committee quality, and broader governance arrangements. By contrast, ESG remains the least consistent and least integrated dimension, as it appears in some studies as a complementary governance mechanism but in others does not clearly restrain tax avoidance. This review highlights role in GCG, ESG, audit quality